Effect of air flow rate and temperature on the atomization characteristics of biodiesel in internal and external flow fields of the pressure swirl nozzle. (15th August 2022) - Ma, Xin; Wang, Shuang; Li, Fashe; Zhang, Huicong; Jiang, Shang; Sui, Meng
Abstract: In this study, the flow and spray of biodiesel in the swirl atomization nozzle were analyzed. The influence of primary air flow rate and temperature on the atomization characteristics in the internal and external flow fields of biodiesel was discussed through simulation and experiments. The velocity of biodiesel in the nozzle and mixing chamber were symmetrically distributed. With increasing primary air flow rate, the maximum speed area increased and the shape of the turbulent kinetic energy of biodiesel changed from columnar to funnel. When the primary air flow rate increased from 10 to 30 L/min, the Sauter mean diameter, (SMD, d32 ) decreased from 95 to 28 μm, and when it increased to 50 L/min, d32 changed slightly. With increasing fuel temperature, the spray velocity increased and the particle size gradually decreased, while the particle size of each interval remained almost unchanged over 45 °C. Therefore, the best primary air flow rate and temperature for the swirling atomization of biodiesel were 30 L/min and 45 °C. It was determined that the increase in air flow rate and temperature promoted the development of atomization flow field and the breaking of droplets in biodiesel, thus optimizing the swirling atomization of biodiesel. Graphical abstract: Image 1 Highlights: The atomization characteristics of biodiesel in industrial furnaces were studied. The velocity of biodiesel in internal flow field was symmetrically distributed. The maximum velocity and turbulent kinetic energy was 17 m/s and 150 m 2 /s 2 . With increasing fuel temperature, the velocity increased, particle size decreased. The best air flow rate and temperature were 30 L/min and 45 °C.